2016
DOI: 10.1016/j.jaci.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma total neopterin and kynurenine/tryptophan levels during pregnancy in relation to asthma development in the offspring

Abstract: Background Neopterin and the kynurenine/tryptophan ratio (KTR) increases with interferon-γ stimulation, indicating Th1-immunity, and thus might be inversely associated with asthma. Objective To examine the association of maternal neopterin and KTR during pregnancy with asthma in the offspring. Methods We analyzed the associations of maternal plasma total neopterin level and KTR in mid-pregnancy with asthma at 7 years among 2,883 children in the Norwegian Mother and Child Cohort Study. Asthma was classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…On the other hand, L‐tryptophan, L‐arginine and L‐kynurenine were significantly increased on the apical compartment of ALI‐cultured Calu‐3 cells after Der p 1 exposure but not on the basolateral one, compared to both, control and Ole e 1‐exposed cells. These metabolites have been associated to allergy 31,32 . The essential amino acid L‐tryptophan is breakdown by the indoleamine 2,3‐dioxygenase (IDO) enzyme in N‐formyl‐kynurenine via the kynurenine pathway, which also include the metabolite kynurenine 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, L‐tryptophan, L‐arginine and L‐kynurenine were significantly increased on the apical compartment of ALI‐cultured Calu‐3 cells after Der p 1 exposure but not on the basolateral one, compared to both, control and Ole e 1‐exposed cells. These metabolites have been associated to allergy 31,32 . The essential amino acid L‐tryptophan is breakdown by the indoleamine 2,3‐dioxygenase (IDO) enzyme in N‐formyl‐kynurenine via the kynurenine pathway, which also include the metabolite kynurenine 33 .…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites have been associated to allergy. 31 , 32 The essential amino acid L‐tryptophan is breakdown by the indoleamine 2,3‐dioxygenase (IDO) enzyme in N‐formyl‐kynurenine via the kynurenine pathway, which also include the metabolite kynurenine. 33 IDO‐1 is the predominant isoform expressed in the lung by epithelial cells among others.…”
Section: Discussionmentioning
confidence: 99%
“…67 There is also great interest in identifying biomarkers that might be reflective of asthma development in utero. Magnus et al 75 reported that high maternal levels of neopterin, a marker of cellular immune activation, during pregnancy were positively associated with asthma in offspring, but further studies are needed to identify the mechanism for this observation. There is also interest in using breathomics with the assessment of volatile organic compounds in assessment of asthma and COPD.…”
Section: Table IV Useful Biomarkers For Personalized Medicine For Asthmamentioning
confidence: 99%
“…Фермент GTP CH I катализирует образование 7,8 -диги-дронеоптеринтрифосфата из ГТФ. Отщепление фосфорных остатков клеточными фосфатазами приводит к образованию 7,8 дигидронеоптери-на, при неферментативном окислении которого и образуется неоптерин [12]. При патологических состояниях, связанных с активацией иммунной системы, концентрация неоптерина и 7,8 диги-дронеоптерина в организме может значительно увеличиваться.…”
Section: неоптерин и Ifnγ при периодонтитеunclassified